The Role of Technology in M&As: A Firm Level Comparison of Cross-Border and Domestic Deals - Rainer Frey; Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Technological change is often hypothesized as one of the main drivers of merger activities. This paper analyzes the role of technology in mergers and acquisitions (M&As) at the firm level. Based on a newly created data set that combines financial information and patent data for public firms in Europe as well as country level variables, we apply a structural model to investigate technology-related motivations behind merger formation. Distinguishing between cross-border and domestic M&As, we find that technological relatedness of the M&A partners reduces uncertainty and the expected risk of failure associated with cross-border acquisitions significantly, whereas there is no evidence for technological complementarities driving domestic M&As. The relevance of technology for cross-border M&As further illustrates the international character of technology markets.
Keywords: O34; O32; C25; G34; 330; domestic versus cross-border M&As; technological relatedness; market relatedness